Kedudukan Anak Luar Kawin Dalam Sistem Hukum di Indonesia - Prasetyo, Abigail; Dwiyatmi, Sri Harini; Alfret, Alfret; Putri, Devina Athalia; Alsabilla, Fadilla Putri (Kertha Patrika, 2023)
This article is aiming to share the legal concept regarding the definitions, regulations and legal relationships and its impact to the illegitimate child. Therefore, the sources of this article will be from the civil law, customary law, Islamic law, and the regulation regarding marriage law in Indonesia. As a normative study, this article is using the conceptual approach and statute approach regarding the topic of illegitimate child. In conclusion to the research, the illegitimate child doesn’t have any legal relationship to their biological father. Moreover, there are no chance for illegitimate child to be a legal child based on customary law and Islamic law. In the end, the legal protection for illegitimate child hasn’t given a legal certainty for the illegitimate child standing completely. Especially when it comes to illegitimate child to have legal relationship to their biological father. To make this happened, the child shall be proven by technology, a DNA test. Therefore, court shall have the ability to force this test, in order to give safety value and legal certainty, especially for the illegitimate child to have legal relationship to their biological father.